INTRAOPERATIVE BREAKAGE OF A REUSED 25 GAUGE ILM PEELING FÓRCEPS - Roy, Madhurima; Roy, Sangeeta; Maiti, Aniruddha; Yadav, Nishita (International Journal of Retina, 2021)
A 59 years male presented with painless diminution of vision in right eye for 4 months. His vision was 20/100 in right eye and 20/30 in left eye. Fundus examination revealed epiretinal membrane in right eye with central macular thickness of 747 μm for which he underwent 25 guage pars plana vitrectomy. Intraoperatively after internal limiting membrane peeling, during removal of the pieces of the membrane from the forceps with the endoilluminator pipe, accidentally one blade from the tip of ILM peeling forceps broke. In this report, we describe first case of inadvertent intraoperative fracture of 25- gauge Grieshaber DSP End-Grasping ILM forceps in a case of ERM who underwent vitrectomy and removal of ERM with successful removal of fractured tip of ILM forceps.